Sustaining Employee Networks in the Virtual Workplace - Levin, Daniel; Kurtzberg, Terri (MIT Sloan Management Review, 2020)
Many organizations began fielding their largest-ever remote workforces during the coronavirus crisis. But that widespread shift to virtual work also poses risks to interpersonal networks within companies. With an understanding of how trust and cooperation might erode, managers can act to bolster good working relationships.
Online resource; Title from title page (viewed May 27, 2020)